PENGARUH LATIHAN PLYOMETRIC DOUBLE LEG SPEED HOP TERHADAP PENINGKATAN KECEPATAN BERENANG GAYA BEBAS PADA ATLET RENANG USIA 9 - 14 TAHUN - Manda Mely Garitny; Ezra Bernadus Wijaya; Wahyuni, Deby Tri (Indonesian Journal of Physiotherapy, 2023)
To swim required mastery of basic techniques. For example, sliding, moving the arms and legs, and taking a breath. The hallmark of freestyle is the whole body in a straight line. The movement of both arms is on the surface of the water. In the freestyle technique, many factors influence to be able to produce maximum swimming speed, including height, arm power and leg muscle strength. This research used a quasi experimental study. Quasi Experiments using the entire sample divided into two speed groups to be treated (treatment) and not given treatment (treatment), and using samples taken randomly. The research design uses Two Group Pre-Test Post-Test. the post-test results in the intervention group and the control group were 0.447 for the intervention group and 0.051 for the control group. The results of the normality test can be concluded that the P value is 0.05, where the resulting hypothesis is normally distributed data (Ho is accepted). In the control group, the result was 0.723. From the hypothesis results obtained, there was no difference or change in freestyle swimming speed for athletes at the Tirta Serayu Banjarnegara Club, so Ho was accepted and Ha was rejected. So it can be concluded that the intervention of Plyometric Double Leg Speed Hop is effective in increasing the speed of freestyle swimming in swimming athletes at the Tirta Serayu Banjarnegara Club.